ANALISIS FAKTOR-FAKTOR YANG MEMICU POTENSI KECURANGAN (FRAUD) (Studi Penelitian Pada Pemerintah Kabupaten Mimika, Papua) - Yusak Naa; Hotman T Pohan (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2019)
The purpose of this study was to examine employee perceptions in government institutions, namely the influence of procedural justice, distributive justice, effectiveness of the internal control system, suitability of compensation, organizational culture, unethical behavior, and law enforcement against fraud in the Mimika Government, Papua. The number of samples in this study were 140 respondents in the Mimika Government, Papua.The results of this study indicate that unethical behavior has a positive effect on fraud potential, law enforcement has no effect on potential fraud, the effectiveness of the internal control system has a negative effect on fraud potential, procedural justice has a negative effect on fraud potential, distributive justice has no effect on potential fraud, suitability compensation does not affect the potential for fraud, and organizational culture does not affect the potential for fraud in the Mimika government sector in Papua.